INTU‐related oral‐facial‐digital syndrome type VI: A confirmatory report. Issue 6 (6th April 2018) - Bruel, A.‐L.; Levy, J.; Elenga, N.; Defo, A.; Favre, A.; Lucron, H.; Capri, Y.; Perrin, L.; Passemard, S.; Vial, Y.; Tabet, A.‐C.; Faivre, L.; et al.
Abstract : Oral‐facial‐digital (OFD) syndromes are a subgroup of ciliopathies distinguished by the co‐occurrence of hamartomas and/or multiple frenula of the oral region and digital anomalies. Several clinical forms of OFD syndromes are distinguished by their associated anomalies and/or inheritance patterns, and at least 20 genetic types of OFD syndromes have been delineated. We describe here a child with preaxial and postaxial polydactyly, lingual hamartoma, a congenital heart defect, delayed development and cerebellar peduncles displaying the molar tooth sign. Whole‐exome sequencing and SNP array identified compound heterozygous variants in the INTU gene, which encodes a protein involved in the positioning of the ciliary basal body. INTU is a subunit of the CPLANE multiprotein complex essential for the assembly of IFT‐A particles and intraflagellar transport. This report of a second patient with INTU ‐related OFD syndrome and the further delineation of its neuroimaging and skeletal phenotype now allow INTU ‐related OFD syndromes to be classified within the OFD syndrome type VI group. Patients display a phenotype similar to that of mice with a hypomorphic mutation of Intu, but with the addition of a heart defect. Abstract : INTU‐ related orofaciodigital syndrome type VI: oral hamartoma, mesoaxial polydactyly and the molar tooth sign.